Methyl Orange Dye Removal through Adsorption using TiO2 modified Montmorillonite Granule - Dewi Yuliana; Erfan Priyambodo (Indonesian Journal of Chemistry and Environment, 2022)
This research was conducted to determine the characteristics of TiO2 modified montmorillonite granule and to determine the effectiveness of its filtration against methyl orange dye. Montmorillonite granule particles were made through a pressing process and continued with sintering at 900oC. The granules obtained were coated with TiO2 photocatalyst by the deep coating method. The montmorillonite granules were characterized using SEM-EDX and the methyl orange dye adsorption process was carried out using the column method. The SEM analysis showed that the granules is porous materials and the EDX confirm the increasing of TiO2 content in montmorillonite before and after being coated with TiO2 from 0.50% to 22.66%. The best adsorption effectiveness of methyl orange was 96.6% at the flow rate of 0.0083 L/hour, which occurred in the use of TiO2 modified montmorillonite granule.